2018
DOI: 10.1111/vec.12715
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the first‐time pass rate of the American College of Veterinary Emergency and Critical Care certifying examination (2010–2015)

Abstract: Between 2010 and 2015 residents trained in academic training programs were significantly more likely to pass the ACVECC certifying examination compared to those trained in private practice training programs. The causes of this difference are uncertain, are likely multifactorial and warrant further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…A previous study identified an association between academic training centers and first-time ACVECC examination success 4 but was unable to identify the factors that underpinned this association.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…A previous study identified an association between academic training centers and first-time ACVECC examination success 4 but was unable to identify the factors that underpinned this association.…”
Section: Discussionmentioning
confidence: 93%
“…A previous study identified an association between academic training centers and first‐time ACVECC examination success 4 but was unable to identify the factors that underpinned this association. The present study reconfirmed this association between academic residencies and examination success and, moreover, identified multiple differences in the characteristics of both the residents and residency programs.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Published analyses of factors associated with board examination pass rates for other veterinary specialty residency programs include ophthalmology, emergency and critical care, and internal medicine. [13][14][15][16] Evaluation of examination performance of candidates of the American College of Veterinary Ophthalmologists (ACVO) and small animal candidates of the American College of Veterinary Emergency and Critical Care (ACVECC), respectively, found higher first-time board examination pass rates for residents in academic programs (AP) compared to private practice (PP). 13,14 Recently, a prospective study found factors associated with first-attempt success of the ACVECC board examination; training at programs with more ACVECC Diplomates, training at programs with more ACVECC residents, and having no requirement to manage both Emergency Room and Critical Care cases simultaneously, were independently associated with firstattempt success.…”
Section: Introductionmentioning
confidence: 99%